Civil Vengeance : Literature, Culture, and Early Modern Revenge - King, Emily L., 1982- (Book collections on Project MUSE., 2019)
"Civil Vengeance changes how we understand retribution and uncovers an archive of revenge literature in early modern England. Shifting attention from episodic revenge to quotidian forms, the author theorizes the manner in which retaliation informs identity formation, interpersonal relationships, and the construction of the social body in early modern England"--